2018
DOI: 10.3389/fphys.2018.00668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training and Competition Load on Neuromuscular Recovery, Testosterone, Cortisol, and Match Performance During a Season of Professional Football

Abstract: Introduction: Training load and other measures potentially related to match performance are routinely monitored in team-sport athletes. The aim of this research was to examine the effect of training load on such measures and on match performance during a season of professional football.Materials and Methods: Training load was measured daily as session duration times perceived exertion in 23 A-League football players. Measures of exponentially weighted cumulative training load were calculated using decay factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 53 publications
4
46
2
Order By: Relevance
“…Therefore, considering the 48 h duration of their acute phase after a football match, the incremental behavior observed in the three games analyzed by this study may be associated with the accumulation of residual muscle damages from previous matches that have not yet been fully regenerated. This hypothesis would reinforce results from previous studies that found an association between athletes' accumulated fatigue during the competitive season and their physiological responses [26,28,46].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, considering the 48 h duration of their acute phase after a football match, the incremental behavior observed in the three games analyzed by this study may be associated with the accumulation of residual muscle damages from previous matches that have not yet been fully regenerated. This hypothesis would reinforce results from previous studies that found an association between athletes' accumulated fatigue during the competitive season and their physiological responses [26,28,46].…”
Section: Discussionsupporting
confidence: 88%
“…Research shows that the volume of sprints performed in a match remains the same even when reducing the time in-between each match [18,19] and that non-contact injuries increase when more than one match is played per week [20][21][22]. Several studies have investi- gated the neuromuscular and physiological responses caused by training and match-play [23][24][25][26][27][28][29]. However, some of the procedures available to measure these responses require that the players perform the same efforts that provoked them in the first place [3,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contradictory to these, Rowell et al 23 Table 2). These results may indicate that players did not sufficiently recover from the previous week of training or match, as it has been found players' physiological stress can take up to 48-hours to reduce to baseline levels post-match.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of the training load on Sal-T, testosterone was increased for both short and long periods of training (3 to 28 days). Although the Sal-T level increased in both periods, the performance improved only for the majority of midfielders [13].…”
Section: Introductionmentioning
confidence: 88%